A Critical Analysis of the Impact of Research in Education: A Systematic Review - Katukula, Kelvin M; Kambeyo, Linus (Namibian Journal for Research, Science and Technology, 2022)
Background: Many studies have demonstrated the impact of research in many spheres of life. With the scientific knowledge on the rise, we postulated that impact of research is evident in different scientific fields, which includes education. It is not easy to provide a scholarly definition of the term impact of research as it lacks a standard definition and has various applications. Its uses ranges measuring specific measures to measuring different phenomena. However, impact of research is a demonstrable contribution outside academia. It is a benefit that society gets because of research activities and one way of archiving this benefit can be through the addition of value and improvement of the quality of life as a consequence of research. From the education perspective, the meaning of the impact of research may include the development of skills, knowledge, values, and cultural norms of a people. It is equally alluded to the ability to transform the art of teaching, which might lead to useful lessons that explain the curriculum to the benefit of the students. The impact of research can also mean the ability to influence the modification of educational policies to align them with the global educational trends. This critical systematic review addresses the gap in knowledge about the impact of research in basic education. It further provides a broader understanding of how the research impact affects teaching approaches, education policy, and how it influences education management. Method: the authors carried out a systematic literature review of peer-reviewed journal articles about the impact of research. Results: it has been demonstrated from the reviewed literature that research has an impact on the teaching approaches, education policy, and education management. Keywords: research, impact, output, evidenced-based, teaching-approaches Paper type: A systematic literature review